Answer:
2300
Step-by-step explanation:
Answer:
2,300
Step-by-step explanation:
When we round to the hundreds place, we make sure the numbers behind the hundreds place are zero. Then we round. Here's the general rule for rounding: If the number you are rounding is followed by 5, 6, 7, 8, or 9, round the number up. In this case we round the 2 in the hundreds place up to three because it is followed by a five.
Kim made 4 batches of this fruit punch recipe. Combine: 90 milliliters of strawberry juice 300 milliliters of pineapple juice 3 liters of apple juice How many liters of fruit punch did Kim make?
Answer:
13.56
Step-by-step explanation:
Each batch makes a total of ...
0.090 +0.300 +3 = 3.39 . . . liters
Then 4 batches makes ...
4 × 3.39 L = 13.56 L
Kim made 13.56 liters of punch.
Final answer:
Kim made a total of 13.56 liters of fruit punch by making 4 batches, with each batch including a combination of strawberry, pineapple, and apple juices.
Explanation:
Kim made 4 batches of fruit punch, each containing 90 milliliters of strawberry juice, 300 milliliters of pineapple juice, and 3 liters of apple juice.
To find the total amount of fruit punch made, we first convert all quantities to liters and then sum them up. Since there are 1,000 milliliters in 1 liter, 90 milliliters is equal to 0.09 liters and 300 milliliters is equal to 0.3 liters.
For one batch, the total liters of juice is:
Strawberry juice: 0.09 litersPineapple juice: 0.3 litersApple juice: 3 litersSo for one batch, the total is 0.09 + 0.3 + 3 = 3.39 liters.
Since Kim made 4 batches, the total amount of fruit punch is:
4 batches × 3.39 liters per batch = 13.56 liters
Therefore, Kim made 13.56 liters of fruit punch in total.
Which of the following is the inverse of y = 6 Superscript x?
y = log Subscript 6 Baseline x
y = log Subscript x Baseline 6
y = log Subscript one-sixth Baseline x
y = log Subscript 6 Baseline 6 x
Answer:
Option A
Step-by-step explanation:
your welcome = )
The inverse of the function y = 6ˣ is y = log₆(x), which means option A is correct.
To find the inverse of the function y = 6ˣ, we need to swap the roles of x and y and then solve for y. The steps to find the inverse are as follows:
Start with the original function: y = 6ˣ
Swap x and y:
[tex]x = 6^{y}[/tex]
To solve for y, take the logarithm of both sides using the same base (in this case, base 6):
log₆x = log₆([tex]6^{y}[/tex])
Since [tex]log_{b} (b^{y} )[/tex] = y, we get: y = log₆x
Therefore, the inverse function is y = log₆x.
Image: ( A regular hexagon has an apothem of 4 and a side length of
8√3 /3 Its area is:_____)
Answer
A) 16√3 sq units
B) 48√3 sq units
C) 64√sq units
D) 32√3 sq units
Answer:
D: 32[tex]\sqrt{3}[/tex]
Step-by-step explanation:
8/3[tex]\sqrt{3}[/tex] * 1/2 * 4 = 16[tex]\sqrt{3}[/tex]/3
16[tex]\sqrt{3}[/tex]/3 * 6 = 32[tex]\sqrt{3}[/tex]
What are the factors of x2 + 3x - 4?
(x + 4) and (x - 4)
(x + 3) and (x-4)
(x + 4) and (x - 1)
(x + 3) and (x - 1)
Answer:
C. (x + 4) and (x - 1)
Step-by-step explanation:
The middle number is 3 and the last number is -4.
Factoring means we want something like
(x+_)(x+_)
Which numbers go in the blanks?
We need two numbers that...
Add together to get 3
Multiply together to get -4
Can you think of the two numbers?
Try -1 and 4:
-1+4 = 3
-1*4 = -4
Fill in the blanks in
(x+_)(x+_)
with -1 and 4 to get...
(x + 4) and (x - 1)
Please help me with this
Step-by-step explanation:
Putting values of c and r
4 + 4(10) - 3(10 - 3)
4 + 40 - 3(7)
44 - 21
23
ооо
Choose the expression that shows the correct product for
Answer:
√36
Step-by-step explanation:
√(a·b) = √a·√b, so
√3·√12 = √(3·12) = √36 = 6
Answer:
√36
Step-by-step explanation:
√3*√12 = √36 = 6
This matches the second answer choice.
proving the converse of the parallelogram side theorem
Answer:
* LOOK AT THE PICTURE's*
I hope this helps and is the right one
The converse of the parallelogram side theorem states, If the opposite sides of a quadrilateral are congruent, then the quadrilateral is a parallelogram.
To prove this statement, we will assume that the opposite sides of a quadrilateral are congruent and demonstrate that it must be a parallelogram.
If both the opposite sides are parallel then we can easily prove that a parallelogram
Given: Quadrilateral PQRS, where PQ is congruent to RS and PR is congruent to QS.
To prove: PQRS is a parallelogram.
Proof:
Since PQ is congruent to RS (given), the segment PQ is parallel to the segment RS by the converse of the corresponding sides of congruent triangles are congruent (CPCTC). Since PR is congruent to QS (given), the segment PR is parallel to the segment QS by CPCTC.
Now we have both pairs of opposite sides of PQRS parallel, which satisfies the definition of a parallelogram.
Therefore, by proving that both pairs of opposite sides are PQRS parallel, we have shown that if the opposite sides of a quadrilateral are congruent, then the quadrilateral is a parallelogram.
This completes the proof of the converse of the parallelogram side theorem.
Learn more about parallelograms here:
https://brainly.com/question/32441125
#SPJ2
A bread recipe calls for 2 cups of wheat flour and 3 cups of white flour. How much flour does the recipe call for
altogether?
Answer:
5
Step-by-step explanation:
3+2=5
Answer:
5 cups
Step-by-step explanation:
2 cups plus 3 cups
BRAINLIEST if right!
What is the equation of the line with a y-intercept of −10 and a slope of 3?
Answer:
y = 3x-10
Step-by-step explanation:
The slope intercept form of a line
y = mx+b where m is the slope and b is the y intercept
The slope is 3 and the y intercept is -10
y = 3x-10
Use the given qualitative data to construct the relative frequency distribution. The 2545 people aboard a ship that sank include 406 male survivors, 1651 males who died, 362 female survivors, and 126 females who died.Complete the relative frequency distribution below. Relative Frequency Category Male survivors % Males who died % Female survivors % Females who died % (Round to one decimal place as needed.)
Answer:
The data that we have is:
total people: 2545
male survivors: 406
male who died: 1651
total males: 406 + 1651 = 2057
female survivors: 362
female who died: 126
total females: 362 + 126 = 488.
We want to know:
for the percentages, we must calculate the quotient between the total numbers of the set, and the number in the particular category we are looking for.
% male survivors = (number of male survivors/total number of males)*100%.
= (406/2057)*100% = 19.73%
% male who died = (1651/2057)*100% = 80.2%
% female survivors = (362/488)*100% = 74.18%
% female who died = (126/488)*100% = 25.82%
Using the circle below, if I double the radius in length, what affect does that have on the new circumference?
Answer:
it will also double the circumference
Step-by-step explanation:
c = 2πr
r' = 2r
c' = 2πr' = 2π x 2r = 4πr
You went to the mall with $52.50. You bought three shirts that each cost x
dollars. Which expression represents the amount of money, in dollars,
that you had left after you bought the shirts? *
Rewrite the equation by completing the square 4x^2 +28x +49=0
The equation 4x^2 + 28x + 49 = 0 is already a perfect square trinomial, and when rewritten in completed square form, it is (x + 7/2)^2 = 0, resulting in the solution x = -7/2.
To rewrite the equation by completing the square for the given quadratic equation 4x^2 + 28x + 49 = 0, we must manipulate the equation so that the left side becomes a perfect square trinomial.
Steps to Complete the Square
Divide all terms by the coefficient of x^2, which is 4 in this case, to make the coefficient of the x^2 term equal to 1.
You now have x^2 + 7x + (49/4) = 0.
Find a number that, when added to x^2 + 7x, completes the square. This number is (b/2)
2, where b is the coefficient of x; thus, here it is (7/2)^2 = 49/4.
Since 49/4 is already present, it confirms that the equation is already a perfect square trinomial.
Therefore, you can rewrite the equation as (x + 7/2)^2 = 0.
Finally, solve for x by taking the square root on both sides of the equation and subtracting 7/2 from both sides to get x = -7/2.
The equation 4x^2 + 28x + 49 = 0 is rewritten in completed square form as (x + 7/2)^2 = 0, with the solution x = -7/2.
Convert the angle 0 = 230° to radians.
Answer:
230° is equal to [tex]\displaystyle \frac{23 \pi}{18}[/tex] radians.
General Formulas and Concepts:
Trigonometry
Degrees to Radians Conversion: [tex]\displaystyle \frac{n\pi}{180}[/tex]
n is the degreesStep-by-step explanation:
Step 1: Define
Identify variables.
n = 230°
Step 2: Find Radians
Substitute in variable [Degrees of Radians Conversion]: [tex]\displaystyle \frac{230 \pi}{180}[/tex]Simplify: [tex]\displaystyle \frac{23 \pi}{18}[/tex]∴ 230° is equal to [tex]\displaystyle \frac{23 \pi}{18}[/tex] radians.
---
Topic: Pre-Calculus
Unit: Trigonometry
what is 11/12 of a full rotation
Answer:
Turn-0.9166666666666666
Degree-330.00000000081860208
Final answer:
11/12 of a full rotation equates to 330 degrees or approximately 2.91 radians.
Explanation:
11/12 of a full rotation in a mathematical context refers to completing 11 out of 12 equal parts of a circle. Since a circle has 360 degrees, we can calculate this portion of a rotation by finding 11/12 of 360 degrees, which is 330 degrees. In terms of radians, since a full rotation is 2π radians, the same portion in radians would be 11/12 of 2π radians, which is approximately 2.91 radians.
Elinor determined that a triangle with side lengths 6, 10, and 8 does not form a right triangle.
62 + 102 = 82
36 + 100 = 64
136 ≠ 64
Is her answer correct?
Answer
No, she should have added 62 and 82 and compared that to 102.
Answer:
The correct answer is C) No, she should have added 62 and 82 and compared that to 102.
Step-by-step explanation:
Her answer is incorrect because she did not follow the steps correctly, she should have added the two numbers. Good luck!
11: Jack is 10 years old.
Kylie is 17 years old.
Vanessa is 23 years old.
Kylie and Vanessa share £16 in the ratio of their ages.
Kylie gives 20% of her share to Jack.
Vanessa gives a quarter of her share to Jack.
How much money does Jack receive?
Answer:
£3.66
Step-by-step explanation:
17+23=40
40=16 what about 17
16×17=272÷40=£6.8
16-6.8=£9.2
20% of £6.8 = £1.36
1/4 of £9.2 = £2.3
1.36+2.3=£3.66
Suppose you wanted to change the state’s constitution to require public financing for all campaigns. If you were relying on professional signature gatherers (who charge at least $1.50 per signature), what is the minimum amount of money you could reasonably expect to spend in order to qualify this amendment for the ballot?
Answer: $1.5 millions
Step-by-step explanation:
Since the population is in millions and a million is like a fraction many millions.
Therefore, the minimum amount of money you could reasonably expect to spend in order to qualify for this amendment for the ballot is $1.5 millions
please hellllllllppppppppppppppppppppppppppp
Answer:
[tex]21^{10}[/tex]
Step-by-step explanation:
First, multiply the 3 and the 7 together, and then "multiply" the exponents -8 and 3. (However, when "multiplying exponents, you're really just adding them together: -8 + 5)
([tex]21^{-5}[/tex])^2
Then, multiply the -5 and -2 together, giving you:
[tex]21^{10}[/tex]
1. A dog is tied to a wooden stake in a backyard. His leash is 3 meters long and he runs around in circles pulling the leash as far as it can go. How much area does the dog have to run around in?
Answer:???
Step-by-step explanation:
Answer:
As the stake is 3 m long we will take it as the radius of the circle and find the area as per:
22/7*3*3=22/7*9=198/7m^2
198/7 metre square.
Sandra save 13% of her salary for retirement. This year her salary was $2000 more than in the previous year, and she saved $5590. What was her salary in the previous year?
Answer:
Sandra's salary the previous year was $41,000
Step-by-step explanation:
Please check the files attached for more explanation
Final answer:
By setting up an equation where 0.13 times Sandra's previous year's salary plus $2000 equals her savings of $5590, we solve to find that Sandra's previous year's salary was $41,000.
Explanation:
To solve the problem of finding Sandra's salary from the previous year, we need to use the information given about her savings and current year's salary increase. Since Sandra saved 13% of her salary and we know that the total amount saved this year is $5590, we can set up the following equation where S represents her salary from the previous year:
0.13(S + 2000) = 5590
Now we solve the equation:
Divide both sides of the equation by 0.13 to isolate S + 2000 on one side:
(S + 2000) = 5590 / 0.13
S + 2000 = 43000
Now subtract 2000 from each side to solve for S:
S = 43000 - 2000
S = 41000
Therefore, Sandra’s salary in the previous year was $41,000.
The price of a watch was increased by 10% to £660. What was the price before the increase?
Answer:
£600
Step-by-step explanation:
First take if 110% equals to £660 what about 100%
100×660 =66000 ÷ 110 =£600
The original price of the watch, before the 10% increase, was £600.
Explanation:The price of a watch was increased by 10% to £660, and we are asked to find the price before the increase. We can solve this problem by considering that the increased price is 110% of the original price. To calculate the original price, let's set up the equation:
660 = 1.10 * Original Price
To solve for the Original Price, we divide 660 by 1.10:
Original Price = £660 / 1.10
This gives us the original price of the watch which is £600.
Learn more about percentage here:https://brainly.com/question/33932701
#SPJ3
need help on this math problem can someone help ax +by=cz
Answer:
a = (cx - by)/x
Step-by-step explanation:
ax + by = cz
ax = cz - by
a = (cx - by)/x
Can I get brainliest
Sophia factored 81y^6 as (9y^3)(9y^2) Ahmed factored 81y^6 as (3y^6)(27y) Which of them factored 81y^6 correctly?
To find if either of them are correct just multiply each of them:
(9y^3)(9y^2)= (9)(9)(y^3)(y^2)
=81y^5
Sophia is incorrect.
(3y^6)(27y)=(3)(27)(y^6)(y)
=81y^7
Ahmed isn't correct either!
Both the persons Sophia and Ahmed do not factor in the expression correctly.
What is an integer exponent?In mathematics, integer exponents are exponents that should be integers. It may be a positive or negative number. In this situation, the positive integer exponents determine the number of times the base number should be multiplied by itself.
It is given that, Sophia factored 81y⁶ as (9y³)(9y²) and Ahmed factored 81y⁶ as (3y⁶)(27y).
We have to find the correct factored form,
= (9y³)(9y²)
The expression is to be arranged in order to find the understand the property of exponent as,
=(9×9)(y³.y²)
=(81)(y³⁺²)
=81y⁵
Thus, both the persons Sophia nor Ahmed do not factor in the expression correctly.
Learn more about the integer exponent here:
brainly.com/question/4533599
#SPJ5
Carlos walked 16 of 20 of school days in February what is the value that is equivalent to the fraction of school days in February that Carlos walked to school . Math
Answer:
70%
Step-by-step explanation:
14 divided by 20
Answer:
6
Step-by-step explanation:
Using the Zero Product Property, solve for the x-values given (x-2)(x+3)=0.
Answer:
x = 2 or -3
Step-by-step explanation:
The product will be zero when one of the factors is zero.
First factor:
x - 2 = 0
x = 2 . . . . . add 2 to both sides of the equation
Second factor:
x + 3 = 0
x = -3 . . . . .subtract 3 from both sides of the equation
The values of x that solve this equation are x = 2 and x = -3.
The Kamp family has twins, Rob and Rachel. Both Rob and Rachel graduated from college 2 years ago, and each is now earning $50,000 per year. Rob is an engineer. The mean salary for engineers with less than 5 years’ experience is $60,000 with a standard deviation of $5,000. Rachel works in the retail industry, where the mean salary for executives with less than 5 years’ experience is $35,000 with a standard deviation of $8,000.
Answer:
$38,000 is correct
Step-by-step explanation:
just took it
The z value is 1.875.
To compare Rob's salary as an engineer to the mean salary for engineers with less than 5 years of experience, we need to find the z-score of Rob's salary.
The z-score formula is
z = (x - μ) / σ,
where x is the given value,
μ is the mean, and
σ is the standard deviation.
Plugging in the values, we get z = (50,000 - 60,000) / 5,000 = -2.
For Rachel's salary as an executive in the retail industry, we use the same process.
The z-score formula is z = (x - μ) / σ, where x is the given value, μ is the mean, and σ is the standard deviation.
Plugging in the values, we get z = (50,000 - 35,000) / 8,000 = 1.875.
Learn more about z-scores here:
https://brainly.com/question/33620239
#SPJ2
How can you find f(2) if f(x)=−3x2−7?
Step-by-step explanation:
F(2)=3(2)²-7
=5
................
Answer:
Square 2. Multiply the result by -3, and then subtract 7.
Step-by-step explanation:
The answer is basically the explanation of the answer. You want to replace x with 2 then square it. You will have 4. Multiply 4 by -3 and you will have -12 then subtract it by 7 and you'll get the answer to f(x). The answer is the steps. Not the 'answer' answer. Hope this helps! (I did this question, and I got it right.)
In 2002, a reproductive clinic reported 41 live births to 152 women under the age of 38, but only 4 live births for 86 clients aged 38 and older. Is there evidence of a difference in the effectiveness of the clinic's methods for older women? Complete parts a through c. Use alphaequals0.05.
Answer:
Difference is (0.181671, 0.263529)
We are more than 95% confident that the true percentage of life births for women under 38 years of age is between 18.17% and 26.35% higher than the true population of live births of women aged 38 or older.
Step-by-step explanation:
We are given;
x1 = 41
n1 = 152
x2 = 4
n2 = 86
Thus,
Sample proportion 1; p'1 = 41/152 = 0.2697
Sample proportion 2; p'2 = 4/85 = 0.0471
For confidence level, 1 - α = 1 - 0.05 = 0.95, using the z-table i attached under the column of z_α/2,we have
z_α/2 = 0.96
The end points of the confidence intervals for p1 - p2 are;
(p'1 - p'2) - z_α/2√[(p'1(1 - p'1)/n1) + (p'2(1 - p'2)/n2)
And
(p'1 - p'2) + z_α/2√[(p'1(1 - p'1)/n1) + (p'2(1 - p'2)/n2)
The first one is calculated as;
(0.2697 - 0.0471) - 0.96√[(0.2697(1 - 0.2697)/152) + (0.0471(1 - 0.0471)/86)
.= 0.2226 - 0.040929 = 0.181671
The second one is calculated as;
(0.2697 - 0.0471) + 0.96√[(0.2697(1 - 0.2697)/152) + (0.0471(1 - 0.0471)/86)
.= 0.2226 + 0.040929 = 0.263529
Thus, we are more than 95% confident that the true percentage of life births for women under 38 years of age is between 18.17% and 26.35% higher than the true population of live births of women aged 38 or older.
You manage a health food store and budget $80 to buy ingredients to make 30 pounds of trail mix. Peanuts cost $2.50 per pound, raisins cost $2.00 per pound, and granola costs $4.00 per pound. If you use twice as many pounds of peanuts as raisins, how many pounds of each ingredients should you buy?
Answer:
8 pounds of raisin, 6 pounds of granola and 16 pounds of peanuts
Step-by-step explanation:
Lets form equations first.
->Peanuts cost $2.50 per pound, raisins cost $2.00 per pound, granola costs $4.00 per pound
2.50p + 2.00r + 4.00g= 80 -->eq(1)
-> bought ingredients to make 30 pounds of trail mix
p+ r+ g= 30 -->eq(2)
->If you use twice as many pounds of peanuts as raisins
2r=p
eq(1)=> 2.50p + 2.00r + 4.00g= 80
2.5(2r) + 2r +4g =80
5r + 2r + 4g =80
7r + 4g =80
eq(2)=>
2r+ r+ g= 30
3r + g =30
-4(3r + g =30)
7r + 4g =80
_______________
-5r = -40
r= 40/5 =>8
For 'g':
3(8) + g =30
g= 6
For 'p':
2r=p
p=16
therefore, 8 pounds of raisin, 6 pounds of granola and 16 pounds of peanuts should be bought
The solution to the problem is to buy 20 pounds of peanuts, 4 pounds of raisins and 6 pounds of granola.
Explanation:This problem requires the use of algebra. Let's denote the amount of peanuts as x, the amount of raisins as y and the amount of granola as z. We have certain constraints according to the problem that need to be satisfied. These are:
2*y = x (since the amount of peanuts is twice that of raisins)x + y + z = 30 (total weight should equal 30 pounds)2.5x + 2y + 4z = 80 (total price should not exceed $80)First, substitute x = 2y from the first equation into the other two equations. This gives you the new equations y + z = 10 and 9y + 4z = 80. Next, solve these simultaneous equations. The solutions are y = 4, z = 6. Substituting y into the first equation gives us x = 2*4 = 20. So, you should buy 20 pounds of peanuts, 4 pounds of raisins and 6 pounds of granola.
Learn more about Simultaneous Equations here:https://brainly.com/question/30319215
#SPJ3